2019
DOI: 10.3390/rs12010100
|View full text |Cite
|
Sign up to set email alerts
|

Sight for Sorghums: Comparisons of Satellite- and Ground-Based Sorghum Yield Estimates in Mali

Abstract: The advent of multiple satellite systems capable of resolving smallholder agricultural plots raises possibilities for significant advances in measuring and understanding agricultural productivity in smallholder systems. However, since only imperfect yield data are typically available for model training and validation, assessing the accuracy of satellite-based estimates remains a central challenge. Leveraging a survey experiment in Mali, this study uses plot-level sorghum yield estimates, based on farmer report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Finally, micro/nanosatellites can provide data in several spectral bands (which are sensitive to the crop structure, leaf pigment, and water content), and they enable meter-levelresolution images for estimating crop phenotyping traits at a very large scale [24], [79], [87], [88], [144], [193], [236], [239]. Micro/nanosatellites include optical and synthetic aperture radar (SAR) satellites.…”
Section: Aerial Phenotyping Platformsmentioning
confidence: 99%
“…Finally, micro/nanosatellites can provide data in several spectral bands (which are sensitive to the crop structure, leaf pigment, and water content), and they enable meter-levelresolution images for estimating crop phenotyping traits at a very large scale [24], [79], [87], [88], [144], [193], [236], [239]. Micro/nanosatellites include optical and synthetic aperture radar (SAR) satellites.…”
Section: Aerial Phenotyping Platformsmentioning
confidence: 99%
“…However, hyperspectral and infrared are more suitable for stand biomass, chlorophyll index [19] [20], pest and disease monitoring [21], etc. UAV images or satellite highprecision images are suitable for biomass of forest stands and tend to check large areas of resources [22].…”
Section: A Backgroundmentioning
confidence: 99%
“…With the commencement of the European Space Agency's Sentinel-2 mission in 2015 and the subsequent surge in the public availability of high-resolution satellite imagery, research has shown the feasibility of satellite-based monitoring of agricultural outcomes in smallholder farming systems (Becker-Reshef et al, 2020;Burke and Lobell, 2017;Jin et al, 2017Jin et al, , 2019Lambert et al, 2018;Lobell et al, 2019Lobell et al, , 2020. Latest advances in satellite imagery and remote sensing techniques have the potential to provide timely insights into conditions on the ground and can fill gaps in agricultural monitoring and statistics (Nakalembe, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-based approaches to mapping agricultural outcomes, such as crop-specific estimates of cultivated areas and yields, require data for training and validating the underlying remote sensing models. The quality and spatial resolution of satellite-based estimates is directly impacted by the data used for model training and validation (Lobell et al, 2019(Lobell et al, , 2020. Recent earth observation research that has focused on low-income countries has relied largely on two sources of training and validation data: (i) manually-labeled optical imagery (DeFourny et al, 2019;Xiong et al, 2017;Wei et al, 2020), 2 and (ii) ground data collection, including as part of household and farm surveys (Hegarty-Craver et al, 2020;Jin et al, 2017Jin et al, , 2019Kerner et al, 2020;Lambert et al, 2018;Richard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%